Analysis of flow and heat transfer over louvered fins in compact geometries - Yong, Kok Wee (2007)
The louvered fin is most widely used in automotive applications. Compared to other geometrical parameters ofthe fin, the louver angle has a stronger effect on heat transfer. This study is carried out by computational method to determine the louver inclination of a rectangular channel heat exchanger that has the greatest influence on flow and heat transfer and invariant with other geometrical parameters. The meshed CAD model is validated with an established correlation in literature. In the earlier years of study, the mean flow angle was defined in two dimensional flows. ANSYS-CFD is capable of defining a mean flow angle was defined in three dimensional flows. The validation agrees weB, with about 5.39% of error. Various graphs are plotted to determine the optimized louver inclination. From the plotted graphs ofNusselt number and pumping power against the Reynolds Number, it is observed that the louver angle has a strong influence on the heat transfer rate. Then, a ratio of heat transfer rate to pumping power is used in the graphs as the nondimensional number representation to determine the optimum angle. In addition to this study, a general correlation is developed to represent the behavior oflouver angle at different ranges of pumping power. With a practical range of Reynolds numbers and louver angles, the optimum angle is found to be 20 degrees. This numerical result has a high confidence level where a good agreement between the meshed models with the established finding is obtained. The study has succeeded in obtaining the result that was set out as the objective.